Effects of Context-Based Teaching Chemistry on Students' Achievement: A Systematic Review - Getu, G.tsadik; Mebrahitu, G.kidan; Yohannes, Goitom (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
This systematic review aims to comprehensively analyze the effect of contextual-based teaching of Chemistry on students' academic achievement. The review includes an analysis of various scholarly articles that have examined the impact of integrating real-world contexts and applications into Chemistry instruction. A total of 10 study articles were selected for further analysis from databases such as ERIC, Scopus, and Google Scholar using a systematic literature review (SLR) method. These studies were thematically organized and reviewed. The interventional context-based (ICB) chemistry study articles employed a range of research designs, including Experimental research method with pre-test-posttest control group design, Experimental research with post-test only design, Quasi-experimental design, and Mixed-method research design, providing a comprehensive examination of the effect of the contextual-based teaching of Chemistry on students' academic achievement. Data analysis methods were utilized, including the independent t-test, one-way t-test, one-way ANOVA or ANOCOA, and MANOVA, to compare means between groups or against specified values. The results of the analysis indicate that context-based chemistry teaching has a positive effect on students' academic achievement. This finding has significant implications for educators, curriculum developers, and policymakers, as it can inform the design of effective Chemistry instruction that enhances students' academic performance. In conclusion, this review highlights the positive impact of contextual-based teaching of Chemistry on student achievement. The findings underscore the importance of integrating real-world contexts and applications into Chemistry instruction. This has implications for educators and policymakers in designing effective teaching strategies to improve students' academic performance in Chemistry. Additionally, the review suggests avenues for future research in this area.